INNOVATIVE LEADERSHIP AS A SUBJECT OF SOCIAL PSYCHOLOGY - Tanirbergen Allambergenovich, Nurabullaev (European Journal of Life Safety and Stability (2660-9630), 2021)
The article is devoted to the topic of innovative leadership as a subject of social psychology. The text also includes innovative leadership, changes in society and personality, socio-psychological qualities of a leading leader, psychological aspects of innovation, psychological components that ensure the qualities of innovative leadership, creative personality and its capabilities, approaches to the problem of innovative leadership, scientific views and phenomenological Aspects. In addition, on the basis of the opinions of many psychologists, the description of the sociopsychological qualities inherent in innovative leaders has been analyzed.